Input of the US advisory panel on federal international tax reform - Weiner, Joann M.; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2006)
In November 2005, the U.S. President's Advisory Panel on Federal Tax Reform released a comprehensive Report titled "Simple, Fair, and Pro-Growth: Proposals to Fix America's Tax System." The Report addressed all aspects of the federal income tax treatment of households and businesses under both domestic and international rules. This paper focuses on the proposals dealing with international elements of federal tax reform that affect multinational businesses. The report presents two broad Plans for improving the U.S. Internal Revenue Code in general and the international aspects of the Code in particular. The Simplified Income Tax (SIT) Plan recommends moving toward a territorial-based income tax system that would exempt active foreign-source business income of foreign branches and controlled foreign subsidiaries at the corporate level and would tax mobile foreign-source income. The Growth and Investment Tax (GIT) Plan recommends moving toward a consumption-based tax system that would tax U.S. businesses on total sales less certain inputs. To highlight the essential aspects dealing with the income tax, this paper will focus on the Simplified Income Tax Plan.
Economic Papers